Low dose oral pH modified release budesonide for maintenance of steroid induced remission in Crohn's disease. Issue 4 (1st April 1998) - Gross, V; Andus, T; Ecker, K W; Raedler, A; Loeschke, K; Plauth, M; Rasenack, J; Weber, A; Gierend, M; Ewe, K; Schölmerich, J; ,
Abstract : Background —The relapse rate after steroid induced remission in Crohn's disease is high. Aims —To test whether oral pH modified release budesonide (3 × 1 mg/day) reduces the relapse rate and to identify patient subgroups with an increased risk of relapse. Methods —In a multicentre, randomised, double blind study, 179 patients with steroid induced remission of Crohn's disease received either 3 × 1 mg budesonide (n=84) or placebo (n=95) for one year. The primary study aim was the maintenance of remission of Crohn's disease for one year. Results —Patient characteristics at study entry were similar for both groups. The relapse rate was 67% (56/84) in the budesonide group and 65% (62/95) in the placebo group. The relapse curves in both groups were similar. The mean time to relapse was 93.5 days in the budesonide group and 67.0 days in the placebo group. No prognostic factors allowing prediction of an increased risk for relapse or definition of patient subgroups who derived benefit from low dose budesonide were found. Drug related side effects were mild and no different between the budesonide and the placebo group. Conclusion —Oral pH modified release budesonide at a dose of 3 × 1 mg/day is not effective for maintaining steroid induced remission in Crohn's disease.